Developing an English for Specific Purposes Need Profile among Library and Information Science Students in Vietnam (Journal of Contemporary Educational Policies and Practices, 2023)
An extensive search of existing literature revealed no research that specifically focused on the needs for English for specific purposes (ESP) of pre-service and in-service librarians within the Vietnamese higher education context. This study aimed to address this gap by developing an ESP needs profile of the pre-service and in-service librarians at a Vietnamese university. Two questionnaires were designed and administered to a total of 185 pre-service and in-service librarians. The results from this study show that both groups of the participants highly valued the importance of ESP. The results also reveal that the perceived needs for the four English language skills (listening, speaking, reading and writing) of the two groups were quite similar, except for reading. In addition, the pre-service and in-service librarians expressed their diverse needs for both academic and occupational English.